PENGARUH MOTIVASI DAN PRAKTEK KERJA LAPANGAN SERTA SARANA PEMBELAJARAN PRAKTEK TERHADAP KESIAPAN KERJA MAHASISWA JURUSAN PARIWISATA POLITEKNIK NEGERI BALI PADA SEKTOR INDUSTRI PARIWISATA - Ni Ketut Narti (PIRAMIDA, 2010)
Every education institute hope to all graduated to be competed in job market, theability to student be able competed in job market if the institute education take steps acorrect decision. The correct decision that is the students have job readiness beforeentering that job. To enter that job is needed most the student motivation, theperformance of practicum facilities to fulfill of medium study to practice readiness tostudent.The aimed of this research is to know: (1) the motivation of influence and influencepractice experience and also medium, either through in group and also private to workreadiness of student (2) to know the dominant influence between motivation, theinfluence practice experience and practicum facilities to work readiness of student.The population of the study was all student of Tourism Politeknik Negeri Balimajoring in tourism industry in the academic year 2008/2009 and the sample of 84students, was established using. The data for each variable were analyzed by means ofdescriptive statistical analyses to find-out any trend appearing in each variable. Toexplore the relationship between the independent and dependent variable, bothindividually and simultaneously, the partial correlation and multiple regression analysis.The result of analysis, quantitative show that: (1) there was influence significantbetween motivation and influence practice experience and also medium of practice tostudent to readiness based on to result of analysis test F with SPSS program version 13found value of F count is 49,529 and Sig value is 0,000. F value (0,05;3;81) is 2,7173.Because F count > F tables hence Ho is refused and Hi is accepted and there was theinfluence of significant by partial between motivation and influence practice experienceand also study of practice to and working readiness. (2) The variable having an effectdominant to influence practice experience (X2) have beta value 0,530 while motivation(X1) have beta value 0,425 and medium of practice study (X3) have beta value 0,258,The conclusion is it most dominant influence to readiness of student is the influencepractice experience.